2019
DOI: 10.31234/osf.io/xkshv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children Persist Less When Adults Take Over

Abstract: Children need to learn to persist through challenges, yet adults sometimes step in to solve problems for them. Here, we looked at how adult taking over related to children’s persistence. In an observational study (N=34, ages 4-8), we found that parents who took over more often during a challenging puzzle task rated their children as dispositionally less persistent. To establish whether taking over can cause reduced persistence, we ran two preregistered experiments (N=150, ages 4-5). Children assigned to a taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We found that children were more engaged with the exhibits when they interacted collaboratively with their caregivers, as compared to when they or their caregivers were leading the interactions. This aligns with results of earlier studies on caregiverchild interactions in museum settings, in which collaborative interactions led to the most engagement (e.g., Medina and Sobel, 2020;Leonard et al, 2021;Sobel et al, 2021;Sobel and Stricker, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…We found that children were more engaged with the exhibits when they interacted collaboratively with their caregivers, as compared to when they or their caregivers were leading the interactions. This aligns with results of earlier studies on caregiverchild interactions in museum settings, in which collaborative interactions led to the most engagement (e.g., Medina and Sobel, 2020;Leonard et al, 2021;Sobel et al, 2021;Sobel and Stricker, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…What might influence whether a child brushes longer on a given day? When children decide whether or not to persist, they consider information about expected utilities (cost and rewards), which is often communicated via adults' behavior (Bandura, 1977;Leonard et al, 2017Leonard et al, , 2020Leonard et al, , 2021Lucca & Sommerville, 2018;Lucca et al, 2019Lucca et al, , 2020. For example, infants and preschoolers pay attention to adults' actions and outcomes and rationally try harder after watching adults' efforts lead to success rather than failure (Leonard et al, 2020;Lucca et al, 2020).…”
mentioning
confidence: 99%
“…We had two competing hypotheses regarding age: Either the effect of condition would be more pronounced in older children, or children across the age span would be equally sensitive to and benefit from pretend play (e.g., White et al, 2017). To further examine the robustness of our findings, we supplemented these analyses with Wilcoxon rank-sum tests, which have been used in the past to examine persistence in young children (e.g., Leonard et al, 2021).…”
Section: Methodsmentioning
confidence: 99%